Questioning profit inflation as an explanation of the post-pandemic inflation - Marc Lavoie (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
The COVID-19 pandemic eventually gave rise to large increases in profits, profit shares and inflation rates. A major controversy has developed among economists and in the media about whether this was largely caused by profit inflation, that is, by increases in the percentage mark-ups set by firms. The paper attempts to clear some confusions regarding the issue of profit inflation, dealing with its definitions and the complexities of its measures. In particular, it shows that increases in economic activity and increases in the relative cost of domestic or imported inputs will lead to an increase in realized profit margins even if percentage mark-ups remain constant. The paper also lists a series of factors that may mitigate the results of empirical studies that show an increase in the aggregate value of this percentage mark-up.
Keywords: D21; E11; E12; E25; E31; 330; Functional income distribution; Imported inflation; Percentage mark-up; Profit inflation